Linguistic Means in Image of COVID-19 (German Political Discourse in Media) - Daniil A. Petrenko; Eduard V. Likhachev; Marina V. Chernyshova (Научный диалог)
The article is focused on the role of lexical and prosodic means of expression in the coverage of the COVID-19 pandemic in German political media discourse. As a research task, the authors identified an attempt to assess the dynamics of the image of the coronavirus phenomenon in the media and to identify the conditionality of the use of linguistic units at certain stages of the pandemic. The material for the study was transcripts and audio recordings of plots from leading German news channels in the first half of 2020. Particular attention is paid to the analysis of the frequency of the use of lexical units and the correlation of lexical and prosodic means of expression. In the course of linguo-stylistic analysis, the main stylistic means are established, depicting the course of the pandemic and the fight against the virus. The prosodic features of the informants' speech, which are determined in the course of the electroacoustic analysis of statements, are brought into consideration. The impact of COVID-19 on all spheres of public life in Germany and its maximum representation in the media determine the relevance of this study. The novelty of the study is seen in the application of a comprehensive methodology for analyzing expressive means in the speech of informants in the period from January to May 2020.